INTERFERENSI FONOLOGIS BAHASA GALELA KE DALAM BAHASA TOBELO - Martina Kihi-kihi, Martina (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT Language is a system of utterance sound symbols used to communicate among the user community. A good language develops based on a system which a set rules obeyed by the users. The term interference was used first by Weinrich (1953) to explain the system changing of a language related to the contiguity of its language with the elements used by bilingual speaker (Chaer and Agustina, 2004:120) Interference means the existence of the deviation or inter language effect. The effect is in the form of the simplest which taking one of the language elements in the relation with other language (Aslinda, 2007:66). Tobelo community is a region who loves the culture or even the dialect sound difference because when they are talking the language inserted with Galela language. The Tobelo community considered as bilingual because they mastered more than one language, it is called interference. Etymologically, the word phonology derives from the combination of the wordÂ  phone which means sound and logywhich means science. Phonologygenerally explains as the basic part in linguistics research hierarchy which learn, discuss, talk, and analyze the sound of language produced by the human vocal cord (Chaer, 2009:1). Phonology is divided into two parts which are phonetics and phonemics. Generally, phonetics can be describe as phonology branchÂ  that research the language sounds without focus on the status, whether the language sounds can differentiate the meaning (words) or not. While phonemics is a branch of phonology research that focus on the language sound that the function as the meaning difference (word) (Chaer, 2009:3) Based on the research, the writer found four factors as the causes of the interference in Tobelo community. They are the bilingual speaker, the presence of mother tongue, geographic location, and mix marriage.